2009
DOI: 10.1111/j.1365-2621.2009.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the conditions of carotenoids production in a synthetic medium by Sporidiobolus salmonicolor (CBS 2636) in a bioreactor

Abstract: This work studied the cultivation conditions for the production of carotenoids by Sporidiobolus salmonicolor (CBS 2636) in a bioreactor. A Plackett-Burman design was used for the screening of the most important factors, followed by a complete second order design, to maximise the concentration of total carotenoids. The maximum concentration of 3425.9 lg L )1 of total carotenoids was obtained in a medium containing 80 g L )1 glucose, 15 g L )1 peptone and 5 g L )1 malt extract, with an aeration rate 1.5 vvm, 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Yeast species Sporobolomyces ruberrimus CBS 2636 has recently been investigated for its potential to produce carotenoid using industrial glycerol from the soap manufacturing process as one of the co-substrates [14,66]. The maximum concentration that could be achieved was 3425.9 µg/L with a carotenoid productivity of 56.9 µg/L/h (41.9 µg/g glycerol).…”
Section: Microbial Conversion Of Glycerol By Yeastmentioning
confidence: 99%
“…Yeast species Sporobolomyces ruberrimus CBS 2636 has recently been investigated for its potential to produce carotenoid using industrial glycerol from the soap manufacturing process as one of the co-substrates [14,66]. The maximum concentration that could be achieved was 3425.9 µg/L with a carotenoid productivity of 56.9 µg/L/h (41.9 µg/g glycerol).…”
Section: Microbial Conversion Of Glycerol By Yeastmentioning
confidence: 99%
“…The data suggest that maximum growth and pigment production was obtained at shaking condition with 120rpm. Bacteria can improve the transfer of substrate and oxygen in aerobic condition [19], similar studies were carried out by the Manish Bhat et al; [2] for production of an orange pigment where optimum shaking condition was found at 120 rpm. …”
Section: Optimization Of Incubation Conditionsmentioning
confidence: 88%
“…The condensation of the two molecules of GGPP leads to the formation of phytoene, the first 40-carbon carotenoid; in turn, these are desaturated to form phytofluene, neurosporene and lycopene [41,42]. Because lycopene is a trans compound, isomerization of the first or second double bond of phytoene occurs in the same stage as the desaturation reaction [43].…”
Section: Carotenoids: Chemical Structures Classification and Biosynthesismentioning
confidence: 99%
“…In the carotenoid pathway in yeasts, γ-carotene appears to be the critical point in the ramification because it acts as the precursor of β-carotene and torulene. In turn, hydroxylation and oxidation of torulene lead to the formation of torularhodin [42].…”
Section: Carotenoids: Chemical Structures Classification and Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation